2020
DOI: 10.2174/1573407215666190219094407
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Effect of Calendula arvensis Flowers is Mediated by Digestive Enzyme Inhibition

Abstract: Background: Calendula arvensis is an annual Mediterranean plant growing in Morocco between Rabat and Khemissat. C. arvensisis is known in folk medicine as an anti-inflammatory and antipyretic remedy. However, few reports have investigated its pharmacological properties. Methods: The objective of the present study was to determine chemical composition of C. arvensis flowers, and to investigate their antidiabetic activities by mean of digestive enzyme inhibition. The profile of phenolic compounds was establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Moreover, the main components isolated; isoquercitrin, isorhamnetin‐3‐ O ‐ β ‐D‐glucopyranoside, 3,5‐di‐ O ‐caffeoylquinic acid and quercetin‐3‐ O ‐(6′′‐acetyl)‐ β ‐D‐glucopyranoside displayed strong inhibition on amylase 39 . Likewise, flower extracts of C arvensis exhibited hypoglycemic effect through inhibition of α‐amylase, α‐glucosidase and ß‐galactosidase, possibly associated with the presence of phenolic compound 40 …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, the main components isolated; isoquercitrin, isorhamnetin‐3‐ O ‐ β ‐D‐glucopyranoside, 3,5‐di‐ O ‐caffeoylquinic acid and quercetin‐3‐ O ‐(6′′‐acetyl)‐ β ‐D‐glucopyranoside displayed strong inhibition on amylase 39 . Likewise, flower extracts of C arvensis exhibited hypoglycemic effect through inhibition of α‐amylase, α‐glucosidase and ß‐galactosidase, possibly associated with the presence of phenolic compound 40 …”
Section: Resultsmentioning
confidence: 95%
“…39 Likewise, flower extracts of C arvensis exhibited hypoglycemic effect through inhibition of α-amylase, α-glucosidase and ß-galactosidase, possibly associated with the presence of phenolic compound. 40 The browning of vegetables, fruits, and fungi and skin hyperpigmentation in humans are two common undesirable phenomena.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“…In vitro investigations showed that some plants were studied in vitro. Indeed, Abudunia et al [ 78 ] have tested the in vitro antidiabetic effects of methanolic, hexane, and aqueous extracts of C. arvensis collected from the region of Khemisset. All tested extracts exhibited enzymatic inhibitory effects on α -amylase, α -glucosidase, and β -glucosidase with some variability.…”
Section: Discussionmentioning
confidence: 99%
“…However, recently, some beneficial properties of the C. arvensis are enhancing the need to thoroughly detail its chemical constitution, also with the objective to fully exploit its properties on human and animal health. The hypoglycaemic activity, exerted mainly through enzyme inhibition, of the aqueous and methanolic extracts of C. arvensis flowers have been demonstrated [79]. The inhibitory activity against αamylase, α-glucosidase, and β-galactosidase was ascribed to caffeic acid and its derivatives.…”
Section: Pfrap and Dpph)mentioning
confidence: 99%